The Impact of the Use of Stairs and Hoops Exercises in the Compatibility and Speed of the Skill Performance of the Players of Ramadi Football Club for Youth (International Journal of Psychosocial Rehabilitation, 2020)
Modern sports training is a search for all new methods and methods through which the player is carrying out exercises in the training units, and that many of its diversity has positive connotations for the players and that the stairs and hoops exercises are very important, especially in this age (youth stage) and where all players serve within the stadium different Their play positions are where their implementation leads to the upgrading of skills as well as interoperability abilities that the players have to a high degree of those abilities and serve the player during difficult and different playing situations in the games, where the goal of the research is the impact of stair exercises. The hypotheses on the compatibility and speed of skill performance of the players, while the imposition of research, show there are statistically significant differences in the values of the search variables (compatibility and speed of skill performance) in the experimental group between the pre- and post-tests and in favor of the post-test. The researchers found that the stairs and hoops exercises have a positive effect on the development of compatibility and skill level of youth football players. The researchers recommend that coaches (especially for junior and youth teams) should be interested in developing the compatibility and skill level of the players for the purpose of training. Recent developments in football.